Staging of rectal carcinoma: MDCT, MRI or EUS. Single center experience - Kocaman, Orhan; Baysal, Birol; Şentürk, Hakan; İnce, Ali Tüzün; Müslümanoğlu, Mahmut; Kocakoç, Ercan; Arıcı, Sema; Uysal, Ömer; Yıldız, Kemal; Türkdoğan, Kürşat; Danalıoğlu, Ahmet (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: To retrospectively compare the efficacy of multidetector computed tomography (MDCT), magnetic resonance imaging (MRI) and endosonography (EUS) in the staging of rectal carcinoma. Materials and Methods: A total of 50 patients (36 male, 14 female) were included in the study. The data from surgical staging were used as reference for comparing the yield of EUS, MRI, and MDCT in preoperative T and N staging of rectal carcinoma. Comparisons were based on the chi-square test. Results: The mean age+SD of the patients were 60±12 years (range; 28-80). The distribution of rectal tumors according to the T and N staging in surgical pathology was as following: T1 (n:2), T2 (n:15), T3 (n:22), T4 (n:11); N0 (n:22), N1-2 (n:28). The accuracy rate of EUS was statistically higher than that of MDCT (92% vs 64%; p<0.01) and that of MRI (92% vs 72%; p<0.01) for T2 tumors. For T3 tumors, EUS had statistically better accuracy of staging compared to MDCT (90% vs 58%; p<0.01) and MRI (90% vs 60%; p<0.01). As for T4 tumors, the accuracy rate of EUS was higher compared to MRI (98% vs 80%; p<0.01). There was no statistical difference in accuracy rates for detection of lymph nodes across the modalities (EUS, 84%; MDCT 76%; MRI 70%; p=not significant). Conclusion: EUS appears more accurate in T staging compared to MDCT and MRI in rectal carcinoma. Regarding nodal staging, performance of EUS, MDCT and MRI are similar.